THE EFFECT OF LOCAL RICE PRICE AND QUALITY ON PURCHASING DECISIONS (CASE STUDY ON KINDAI LIMPUAR MARKET) - Ilhamiyah Ilhamiyah; Ana Zuraida; Mahruzi Mahruzi (UPT Publication and Journal Management, Islamic University of Kalimantan, 2025)
This study investigates the influence of price and product quality on consumer purchasing decisions for local rice, utilizing a case study approach and multiple linear regression analysis. The objectives are to determine (1) the partial impact of price and product quality, (2) the extent of their individual influence, and (3) the combined effect of these variables. The findings reveal that both price and product quality significantly and positively affect consumers’ decision-making, both when evaluated independently and jointly. The coefficient of determination (R²) is 0.375, indicating that 37.5% of the variation in consumer decisions can be explained by the combined influence of price and product quality. This highlights the relevance of economic and qualitative factors in shaping consumer behavior, suggesting that improvements in either attribute could enhance market competitiveness for local rice. Overall, the results emphasize the strategic importance of understanding and leveraging pricing and product standards in agricultural marketing efforts.